PENGARUH AUDIT KINERJA TERHADAP AKUNTABILITAS PUBLIK PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA MAKASSAR - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2016)
This study was to determine whether the performance audit of the positive and significant impact on public accountability of the Regional Water Company (PDAM) Kota Makassar. The method of analysis used in this research is simple regression analysis with the help of Statistical Product and Service Solution (SPSS) version 19. Based on the results of research and discussions that have been raised about the Influence of Audit and Performance Against Public Accountability at the Regional Water Company (PDAM) Kota Makassar , it can be concluded that the performance audit and significant positive effect on the public akuntantabilitas Regional Water company (PDAM) Kota Makassar, if a performance audit on the local water company (PDAM) Kota Makassar both the public accountability is also good.